Perioperative Transgender Hormone Management: Avoiding Venous Thromboembolism and Other Complications. Issue 4 (29th March 2021) - Hontscharuk, Rayisa; Alba, Brandon; Manno, Catherine; Pine, Elyse; Deutsch, Madeline B.; Coon, Devin; Schechter, Loren
Abstract : Summary: This review discusses the current evidence regarding perioperative hormone therapy for transgender individuals, with an emphasis on strategies to reduce the risk of perioperative venous thromboembolism. Historically, surgeons routinely discontinued estrogen therapy in the perioperative period with the goal of reducing the risk of venous thromboembolism. However, abrupt estrogen cessation may also lead to adverse emotional and physiologic effects, including an exacerbation of one's gender dysphoria. The data on the relationship of feminizing hormones and venous thromboembolism in the perioperative setting are largely based on extrapolation of hormone regimens that are no longer in use and may not accurately reflect the actual risk of venous thromboembolism. Future studies will allow surgeons to engage in evidence-based, patient-centered, informed consent while also minimizing the risk of complications, such as venous thromboembolism.